Bottom-up electrochemical preparation of solid-state carbon nanodots directly from nitriles/ionic liquids using carbon-free electrodes and the applications in specific ferric ion detection and cell imaging. Issue 10 (18th February 2016) - Niu, Fushuang; Xu, Yuanhong; Liu, Mengli; Sun, Jing; Guo, Pengran; Liu, Jingquan
Abstract : Solid-state carbon nanodots were generated from nitriles/ionic liquids via a bottom-up electrochemical strategy and successfully used in specific Fe 3+ detection and bioimaging. Abstract : Carbon nanodots (C-dots), a new type of potential alternative to conventional semiconductor quantum dots, have attracted numerous attentions in various applications including bio-chemical sensing, cell imaging, etc., due to their chemical inertness, low toxicity and flexible functionalization. Various methods including electrochemical (EC) methods have been reported for the synthesis of C-dots. However, complex procedures and/or carbon source-containing electrodes are often required. Herein, solid-state C-dots were simply prepared by bottom-up EC carbonization of nitriles ( e.g. acetonitrile) in the presence of an ionic liquid [ e.g. 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF6 )], using carbon-free electrodes. Due to the positive charges of BMIM + on the C-dots, the final products presented in a precipitate form on the cathode, and the unreacted nitriles and BMIMPF6 can be easily removed by simple vacuum filtration. The as-prepared solid-state C-dots can be well dispersed in an aqueous medium with excellent photoluminescence properties. The average size of the C-dots was found to be 3.02 ± 0.12 nm as evidenced by transmission electron microscopy. Other techniques such as UV-vis spectroscopy, fluorescence spectroscopy, X-ray photoelectron spectroscopy and atomic force microscopy were applied for the characterization of the C-dots and to analyze the possible generation mechanism. These C-dots have been successfully applied in efficient cell imaging and specific ferric ion detection.